Investigation of the Soil Depths Temperature Trend Using Parametric and Non-Parametric Methods (Shahrud Station) - S. Shiukhy Soqanloo; S. Golshan; M. Khoshravesh (علوم آب و خاک, 2019)
The effects of climate change can be released from the surface to the soil depth, thereby affecting soil thermal regime. Thermal energy in the soil plays a very important role in causing climate changes. In this study, for the assessment and detection of  the climate changes, soil depths temperature, the measured data related to the  daily air temperature at a height of 2 meters (screen) during the years (1951-2014), and the soil depths daily temperature (5-10-20-30-50 to 100 cm), for 3, 9 and 15 hours, were obtained during a period (1992-2014) in Shahrud station. The climate change detection was employed to compare the treatment mean. As well, for detection of trends related to the annual, seasonal and monthly time series and their relation to the soil depths temperature, parametric methods (regression analysis and Pearson) and nonparametric (Mann-Kendall, Spearman) were applied. The results showed that the soil temperature was increased in all months except January, February and March. Also, in the seasonal time series, the soil depths temperature was increased in all seasons except winter. In fact, based on the results, the soil temperature in spring, summer and autumn was increased. Detection trends of the annual soil depths temperature showed that, except for the Pearson correlation coefficient method, soil temperature was increased at all soil depths.